Assessing the Impact of Electronic Court Systems on the Efficiency of Judicial Processes in the Era of Digital Transformation - Djamaludin Djamaludin; Muhammad Fahruddin Aziz; Yanuriansyah Ar-Rasyid; Iskandar Ali As-Sayyis (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
The E-court system promotes the transparency and efficiency globally, however, the Eastern Indonesian courts face challenges due to infrastructure and literacy. Nonetheless, its benefits are crucial for the justice system modernization. This study evaluated the E-court system’s effect on the judicial process’s efficiency in the Religious and District Courts of Biak Numfor using a quantitative research methodology. A survey was conducted on 100 respondents to assess the user satisfaction and system effectiveness, especially in remote areas. The data were analyzed using descriptive analysis and simple linear regression, which will provide valuable insights. The findings indicate that the E-court system significantly and positively affects the judicial process’s efficiency, and users found it efficient, user-friendly, reliable, secure, and satisfactory. While the quantitative approach provides valuable insights, it also has limitations. Therefore, the study suggests that a qualitative approach could provide a deeper understanding of how information technology affects the justice system. The research results can be useful to the courts in other areas that are considering implementing comparable technologies to enhance process efficiency and user friendliness. In conclusion, the E-court system is a promising technology that can significantly improve judicial process’s efficiency and effectiveness. However, further research is a necessity to understand how information technology affects the justice system, and a combination of quantitative and qualitative approaches may provide a more comprehensive understanding.